Spontaneous Rupture of an Adrenal Artery in Pregnancy: A Case Report - D. Bolla; V. Schyrba; G. Drack; S. Dietler; R. Hornung (Case Reports in Obstetrics and Gynecology)
A spontaneous rupture of an adrenal artery is a rare cause of abdominal pain in pregnancy. We present a case of a pregnant woman who needed to be operated on because of a rupture of the right adrenal artery associated with a fetal bradycardia. An immediate caesarean section was performed. The intra-abdominal palpation identified an extensive retroperitoneal mass near the right kidney and a postoperative computer tomography confirmed an active bleeding near the kidney. For this reason our interventional radiology team, using a right femoral artery approach, performed a flush aortogram and identified the source of bleeding in the right adrenal artery. After two attempts, a coiling of the artery stopped the haemorrhage. The pathogenesis of arterial haemorrhage is still poorly understood although a possible cause could be the excess of hormones during pregnancy, which can lead to a significant arterial wall degeneration. In case of a retroperitoneal bleeding and if the patient is still haemodynamically stable, a transcatheter embolization using microcoils must be considered. This technique is nowadays safe and effective and can be performed within a short time with a lower risk of complications.